Secrets of the greatest snow on earth: weather, climate change, and finding deep powder in Utah's Wasatch mountains and around the world - Steenburgh, Jim, author; Utah State University Press, publisher (Colorado State University. Libraries, 2014)
Snowriders in Utah have long claimed to have the best snow on Earth. Some contend that moisture from the Great Salt Lake fuels storms, while the western deserts dry out the snow to create light, magic flakes. In Secrets of the Greatest Snow on Earth, Jim Steenburgh investigates Wasatch weather lore, exposing the myths, explaining the reality, and revealing why Utah's powder lives up to its reputation. Chapters explore mountain weather, avalanches and snow safety, historical accounts of weather events and snow conditions, and the basics of weather and climate forecasting. Steenburgh explains what creates the best snow for skiing and snowboarding in accurate and accessible language and illustrates his points with 150 color photographs, making Secrets of the Greatest Snow on Earth a helpful tool for planning vacations and staying safe during mountain adventures. This insider's guide to the weather and climate of the Wasatch Mountains also serves as a guide to mountain weather and snow climates around the world. Snowriders, weather enthusiasts, meteorologists, students of snow science, and anyone else who dreams of deep powder and bluebird skies will want to get their mittens on Secrets of the Greatest Snow on Earth.--Provided by publisher.
The secrets -- Wasatch microclimates -- Beyond Utah -- Flaky science -- Lake effect -- Alta goes to war -- Beyond the ropes -- Powder prediction -- Global warming.
Keywords: Climatic changes; Global warming; Weather